Extended Theoretical Framework of Parental Internet Mediation: Use of Multiple Theoretical Stances for Understanding Socio-Ecological Predictors - Iqbal, Sarosh; Zakar, Rubeena; Fischer, Florian (Frontiers in Psychology, 2021)
Digital media is a common phenomenon in contemporary societies. Recognizing the popularity of digital and online devices among the younger generation, the subject of parental internet mediation is of utmost significance for avoiding the adverse effects of digital media on the physical, cognitive, and social wellbeing of youngsters. Taking insights from an informed review of multi-grounded theories, we propose an extended framework of socio-ecological predictors concerning parental internet mediation. This contribution offers an innovative methodological and analytical perspective to consider both psychological and behavioral predictors for promoting resilience. This review acknowledged resilience as a strength-based measure to ensure online safety among young individuals. This review suggests that an integrated socio-ecological approach is critical to formulating the basis for a theoretical framework to fully comprehend the socio-ecological predictors of parental internet mediation.